Analisis Efektivitas Pembelajaran Matematika Menggunakan Interactive Flat Panel - Indraniati Staimen, Selfina; Kurniantoro, Catur; Astuti, Puji; Setyarini, Tanti; Arsi, Fakhrizal; Hasbulloh, Hasbulloh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effectiveness of utilizing Interactive Flat Panel (IFP) in mathematics learning at SMAN 18 Bekasi, including its implementation, impact on student motivation and learning outcomes, and the influencing factors. The method used is a descriptive qualitative approach with data collection techniques through classroom observations and semi-structured interviews with three mathematics teachers and three students selected purposively based on their level of mathematical ability. The results show that the use of IFP is able to increase student motivation, teacher–student interaction, and conceptual understanding through the use of visual media such as graphs and videos, although several technical obstacles were identified, including unstable internet connections, power outages, and difficulties in using the device. In conclusion, the use of IFP is proven to be effective in supporting mathematics learning, provided that adequate technical support and teacher competence in managing technology-based learning are ensured. Keywords: Interactive Flat Panel, Learning Effectiveness, Mathematics, Motivation, Qualitative